SMEs, Social Capital and the Common Good - Spence, Laura J. (Journal of business ethics, 2003)
In this paper we report on empirical research which investigates social capital of Small and Medium Sized Enterprises (SMEs). Bringing an international perspective to the work, we make a comparison between 30 firms located in West London and Munich in the sectors of food manufacturing/production, marketing services and garages. Here we present 6 case studies, which we use to illustrate the early findings from this pilot project. We identify differences in approach to associational membership in Germany and the U.K., with a greater propensity to "belong" to an official group in Germany. We distinguish clear sectoral similarities across the countries, and indications that certain personality types will seek out engagement and find time beyond busy work life schedules, often merging work/home/leisure life and friends. Some of our cases illustrate that formal institutions, networks and mutual relationships can develop social capital for the SME, although we should take care not to assume a universal win-win situation for those who are engaged and contribute to the common good. Some of the obstacles to co-operation and civic engagement are outlined.